BUDAYA HIBRIDA MASYARAKAT CIREBON - M. Alie Humaedi (Humaniora, 2013)
Cirebonis is one of the major of economic distribution network in the archipelago. This city has created a network of its own culture, so many social transformations and their cultural phenomena often appear in different forms with centers of cultural mainstream, both culture (and language) Sundanese or Javanese. The research question is how hybrid’s culture formed according to the city growth?. How cultural hybridity practice is a process of cross-cultural as genealogical heritage of community? Studies using ethnographic approach through in-depth interviews and direct observation was about to explain how Cirebon community articulate their views on the city and the mapping of the ethnic relationship, which is between the Sundanese as owner of the mainstream culture with Wong Java (Java Koek) as the holder of marginal culture. This study found that the cross-cultural process have resulted in cultural hybridityis never clearly demarcated. It could even give birth to new cultural patterns that are more inclined to the mainstream culture, oral so the marginal culture, as seen in the case of cross-cultural marriage that gave to the language selection, the Sunda Koek or Jawa Koek, different with each cultural center